2021
DOI: 10.1038/s41598-021-88441-y
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative stroke before cardiac surgery does not increase risk of postoperative stroke

Abstract: The optimal time when surgery can be safely performed after stroke is unknown. The purpose of this study was to investigate how cardiac surgery timing after stroke impacts postoperative outcomes between 2011–2017 were reviewed. Variables were extracted from the institutional Society of Thoracic Surgeons database, statewide patient registry, and medical records. Subjects were classified based upon presence of endocarditis and further grouped by timing of preoperative stroke relative to cardiac surgery: Recent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, several studies have shown that patients with preoperative stroke have a low risk for hemorrhagic transformation during surgery. 18,19 Our findings are consistent with previous work by Thuny et al…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, several studies have shown that patients with preoperative stroke have a low risk for hemorrhagic transformation during surgery. 18,19 Our findings are consistent with previous work by Thuny et al…”
Section: Discussionsupporting
confidence: 94%
“…In clinical practice, preoperative neuroimaging may be useful to risk stratify patients prior to cardiac surgery given that anticoagulation is often used intraoperatively. However, several studies have shown that patients with preoperative stroke have a low risk for hemorrhagic transformation during surgery 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…When haemodynamic disturbances are present, surgery should be pursued without delay (see Figure 11 and Recommendation Table 17). 451,468,473,567,568,[570][571][572][573][574][575][576][577][578] A more common situation occurs when surgery is considered for the prevention of recurrent embolism after stroke, due to the presence of large vegetations (>10 mm). In patients that have suffered a transient ischaemic attack, the risk of surgery is usually low and surgery should be performed without delay.…”
Section: Timing Of Surgery After Ischaemic and Haemorrhagic Strokementioning
confidence: 99%
“…The critical task at hand is the optimization of the patient before surgery. This may require a postponement of the surgery, but there is a relative paucity of data to guide optimal timing [77,78]. Some advanced computational techniques (artificial intelligence) may help determine the optimal procedure timing, allowing more time for patient optimization [74].…”
Section: Preoperative Periodmentioning
confidence: 99%